2005
DOI: 10.1007/s00417-005-1124-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contour tonometry versus Goldmann applanation tonometry: a comparative study

Abstract: In eyes with normal corneas, DCT allows suitable and reliable IOP measurements which are in good concordance with GAT. Comparison of DCT with intracameral manometry is desirable in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
67
8
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 31 publications
19
67
8
11
Order By: Relevance
“…[20][21][22][23][24] In our series, GAT showed a significant correlation with CCT, contrary to DCT. In accordance with other studies, 6,11,17,25 we observed that CCT affects GAT IOP measurements. We also demonstrated that GAT measurements are lower than DCT readings in corneas with CCTs o600 mm, but they become higher in thick corneas (CCT4600 mm).…”
Section: Discussionsupporting
confidence: 93%
“…[20][21][22][23][24] In our series, GAT showed a significant correlation with CCT, contrary to DCT. In accordance with other studies, 6,11,17,25 we observed that CCT affects GAT IOP measurements. We also demonstrated that GAT measurements are lower than DCT readings in corneas with CCTs o600 mm, but they become higher in thick corneas (CCT4600 mm).…”
Section: Discussionsupporting
confidence: 93%
“…Most studies have found DCT readings to be higher than GAT. 25,26 In contrast, a recent study on African-American subjects did not find a significant difference in mean IOPs between GAT and DCT; with mean DCT IOP only 0.4 mm Hg higher than GAT. 27 This study found no proportional bias between the GAT and DCT readings.…”
Section: Discussionmentioning
confidence: 70%
“…This finding is in agreement with other studies that showed that the difference between the tonometers declined as CCT increased. 36,41 On the contrary, only Barleon et al 35 observed that the difference between the two instruments was greatest in eyes with lower IOP value, gradually lessening as IOP increased. Considering the values recorded in our limited study population, we found an inverse association between DCT and GAT for CCT values above 620 mm and IOP values above 24 mmHg.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results, in spite of different mean values, have been reported by previous investigations. 16,[19][20][21][23][24][25][26][27][28][29][30][31]35,36 The DIOP between DCT and GAT readings was higher in healthy than in glaucomatous eyes, either with open-angle or angleclosure phenotypes (Table 1). The same outcome has been found by analysing IOP measurements obtained by DCT and GAT in different groups of subjects with the same CCT value, except for POAG subjects with thinner corneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation